2006
DOI: 10.1007/s00484-006-0059-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the pollen seasons of the early flowering trees Alnus spp. and Corylus spp. in Worcester, United Kingdom, 1996–2005

Abstract: Previous work on Betula spp. (birch) in the UK and at five sites in Europe has shown that pollen seasons for this taxon have tended to become earlier by about 5-10 days per decade in most regions investigated over the last 30 years. This pattern has been linked to the trend to warmer winters and springs in recent years. However, little work has been done to investigate the changes in the pollen seasons for the early flowering trees. Several of these, such as Alnus spp. and Corylus spp., have allergens, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 34 publications
(30 reference statements)
5
78
1
Order By: Relevance
“…For Corylus, pollen deposition is correlated with precipitation in February and in July of the flowering year. Emberlin et al (2007) found that rainfall had no impact on the start date of the pollen season for Corylus in England, but in Draved February rain seems to favour pollen dispersal. The correlation to July precipitation, which occurs after the flowering season, is most probably spurious.…”
Section: Effects Of Precipitationmentioning
confidence: 91%
“…For Corylus, pollen deposition is correlated with precipitation in February and in July of the flowering year. Emberlin et al (2007) found that rainfall had no impact on the start date of the pollen season for Corylus in England, but in Draved February rain seems to favour pollen dispersal. The correlation to July precipitation, which occurs after the flowering season, is most probably spurious.…”
Section: Effects Of Precipitationmentioning
confidence: 91%
“…Different aerobiological studies, based on long historical databases, have shown earlier pollen seasons during recent years as a result of temperature increase, most of them related to spring fl owering trees (Garcia-Mozo et al 2006 ;Galán et al 2005 ;Emberlin et al 2007 ;Damialis et al 2007 ;Frei and Gassner 2008 ;Bono fi glio et al 2009 ;Orlandi et al 2009 ). The greater advances observed in earlier rather than later spring pollen seasons are probably due to the higher dependency on temperature of early spring tree species, such as hazel, alder and birch.…”
Section: Climate Impacts On the Timing Of Pollen Seasonsmentioning
confidence: 98%
“…a moderate increase of temperature resulted in a delay in winter/early spring tree pollen season start (Emberlin et al 2007 ;Tedeschini et al 2006 ) . It also depends on regional characteristics Recio et al 2009 ) , what may confound patterns.…”
Section: Climate Impacts On the Timing Of Pollen Seasonsmentioning
confidence: 98%
See 1 more Smart Citation
“…Emberlin et al (1997) found a trend to earlier Betula pollen seasons that was related to an increase in cumulative temperatures over 5.5°C in January, February and March. Furthermore, they detected a significant positive relationship between the start dates of the Corylus pollen season and temperatures in October suggesting that lower temperatures in October result in an earlier onset, and vice versa (Emberlin et al 2007). They found a significant negative association between onset and December temperatures indicating that higher December temperatures will produce an earlier onset of Corylus flowering and vice versa (Emberlin et al 2007).…”
Section: Introductionmentioning
confidence: 97%